Las colecciones de leguminosas efectuadas por George B. Hinton, depositadas en el herbario de Royal Botanic Gardens, Kew - Rico Arce, María de Lourdes; Rodríguez, Amparo; Moreno-Gutiérrez, Elizabeth (Instituto de Ecología, A.C., 2008)
A database of specimens of the Legume family collected by George Bool Hinton and deposited in the Herbarium at Kew was elaborated. A summary of these collections is given; it includes a check-list of species ordered by subfamily, indicating Hinton’s collection numbers and type material. The complete database is available to consult in the Global Net on Biodiversity Information and the HerbCat, Kew.